Respostas

2014-02-07T21:06:32-02:00
Olá,
se a parábola tangencia o eixo das abcissas, então a equação tem apenas 1 raiz, em outras palavras, o delta é igual a zero:

 2x² - cx + (c - 2)
Δ = c² -4.2.(c-2) = 0
c² - 8.(c-2) = 0
c²-8c+16 = 0

outra equação :
Δ = 64 - 4.1.16
Δ = 64 - 64
Δ = 0
(8+-0) / 2 = 
4
c = 4

2x² - cx + (c - 2) =  0
2x² - 4x + 2 = 0

f(f(2))

f(2) = 
2x² - 4x + 2 =
2.2² -4.2+2 = 
2.4 -8 + 2 = 
8-8 + 2 = 
2

f(f(2)) = 
2x² - 4x + 2 = 
2.2² - 4.2 + 2 =
2.4 - 8 + 2 = 
8-8 + 2 = 
2